Improvement of the Sequelae of Peripheral Facial Nerve Palsy in a Patient with Hemophilia Mainly Treated with Facial Chuna Manual Therapy: A Case Report - Geumm Mi Lee; Jae Hyung Kim; Ga Young Choi; Jung Hee Lee; Jae Soo Kim; Hyun Jong Lee (MEDrang Inc., 2024)
A patient with sequelae of peripheral facial nerve palsy (FNP) was mainly treated with facial chuna manual therapy (FCMT) for over 6 months. The patient was diagnosed with hemophilia B and C, so invasive treatments, such as acupuncture and pharmacopuncture, were precluded. The facial nerve grading system 2.0 (FNGS) and the House-Brackmann Grading Scale (HBGS), Peitersen, Murata, Mehta, and numeric rating scale (NRS) systems were used to measure treatment effectiveness. Each scale showed improvement: FNGS, 3 to 2; HBGS, 3 to 2; Peitersen scale, 2 to 1; Murata scale, 9 to 4; Mehta scale, 14 to 1; and NRS, 8.5 to 2.5. An overall improvement was evident in facial muscle strength, particularly in synkinesis. If acupuncture and pharmacopuncture are unavailable, FCMT alone may be effective in treating FNP sequelae.